A PATRA DIMENSIUNE A TIMPULUI ŞI ISTORICITATEA ÎN PEDAGOGIE - USM ADMIN (Moldova State University, 2008)
In this paper we start with a question which is a ways that always leads to an answer, an answer which determines a mind transformation: Does the fourth time dimension really exist and if it does then which is its relation with history in pedagogy.